Assessment of the possibility of foam glass application in the sub-ballast layers - Ižvolt, Libor; Dobeš, Peter; Holešová, Michaela; Navikas, Deividas (Journal of Civil Engineering and Management, 2023)
The paper investigates whether foam glass could reduce the structural thickness of the protection layer in the construction of the railway track (saving of natural materials – crushed aggregate) and, at the same time, also provide sufficient thermal protection of the frost-susceptible subgrade surface. It also discusses whether the incorporation of foam glass would have a relevant effect on the increase of the deformation resistance of the railway track structure at the level of the sub-ballast upper surface. Following these assumptions, the paper presents the results of experimental measurements of the deformation resistance of the modified structural composition of the sub-ballast layers (with an embedded foam glass layer) and their comparison with the results determined on a structure with a standard composition of the sub-ballast layers (crushed aggregate sub-ballast layer/protective layer). Also, numerical and mathematical analysis of the influence of the built-in thermal insulation foam glass layer on the reduction of the structural thickness of the protective crushed aggregate layer in terms of the effect of climatic factors is conducted in the paper. The mathematical model, developed by the research, provides the possibility of continuous monitoring of the change in the railway track structure freezing depending on climatic characteristics.